Usage of Neural Networks for ASM Research - Hayk E. Nahapetyan (Изд-во НАН РА)
Purpose of this paper is to describe the possible usage of artificial neural networks for Abelian Sandpile model research. For developing neural networks, Neuroph Studio has been chosen, and Abelian sandpile model has been considered on 2-dimensional grid.
Keywords: Mathematics